2012
DOI: 10.3109/09638288.2011.626486
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of whole body vibration exercise in older people: a systematic review

Abstract: Whole body vibration training may improve strength, power and balance in comparison with a control group, although these effects are not apparent when compared with a group that does conventional exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 38 publications
7
70
0
3
Order By: Relevance
“…34 A systematic review on whole-body vibration programs (combined with strength and dynamic exercises) have shown some benefit compared with a control group (which did the same exercise as the intervention group but without a vibration platform) but not compared with a conventional group (which performed specific exercises based on guidelines of the American College of Sports Medicine). 35 Similar to the results of studies involving community-dwelling older adults, multicomponent interventions to prevent falls in all settings decreased the number of falls and injuries from falls (relative risk 0.91, 95% CI 0.82-1.02, and in number of fall-related injuries relative risk 0.90, 95% CI 0.68-1.20). 36 One systematic review found an improvement in patients' quality of life with evaluation of the extent to which measurement of a person's participation in interventions to prevent falls (as assessed by the individual's functioning in his or her various life roles) was reported in trials of such interventions.…”
Section: Reviewsupporting
confidence: 70%
See 1 more Smart Citation
“…34 A systematic review on whole-body vibration programs (combined with strength and dynamic exercises) have shown some benefit compared with a control group (which did the same exercise as the intervention group but without a vibration platform) but not compared with a conventional group (which performed specific exercises based on guidelines of the American College of Sports Medicine). 35 Similar to the results of studies involving community-dwelling older adults, multicomponent interventions to prevent falls in all settings decreased the number of falls and injuries from falls (relative risk 0.91, 95% CI 0.82-1.02, and in number of fall-related injuries relative risk 0.90, 95% CI 0.68-1.20). 36 One systematic review found an improvement in patients' quality of life with evaluation of the extent to which measurement of a person's participation in interventions to prevent falls (as assessed by the individual's functioning in his or her various life roles) was reported in trials of such interventions.…”
Section: Reviewsupporting
confidence: 70%
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] These reviews included studies involving older patients living in various settings (e.g., the community, acute care hospitals and long-term care institutions). Both single and multiple interventions have been tested.…”
Section: Are There Any Tools To Help Assess the Risk Of Falling?mentioning
confidence: 99%
“…Whole-body vibration (WBV) therapy has recently attracted renewed interest as a method for treating elderly individuals and patients with nervous and/or musculoskeletal defects; one report has described the efficacy of a shortterm WBV program in improving lower-limb muscle strength and power, bone density, and functional mobility, as well as in preventing falls in the elderly (Sitja-Rabert et al 2012). Another study has compared patients who underwent WBV plus exercises with sedentary control groups; however, this disallowed definitive conclusions regarding the contribution of WBV to musculoskeletal improvements (Roelants et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Si bien el entrenamiento de fuerza y resistencia han demostrado ser eficaces para la disminución de caídas en adultos mayores, el entrenamiento mediante vibraciones de cuerpo completo ha mostrado mejoras en la velocidad de caminata, el equilibrio, fuerza y potencia muscular del miembro inferior (Bautmans, Van Hees, Lemper, & Mets, 2005;A. Bogaerts, Delecluse, Claessens, & cols., 2007.;Madou & Cronin, 2008;Rees, Murphy, & Watsford, 2008;Sitjà-Rabert et al, 2012), las cuales han mostrado relación con el riesgo de caída en los adultos mayores.…”
Section: Introductionunclassified